Integration of Capital Market Indices in Asian Countries with Potential Contagion Effects - Ananda, Diyohansyah Chrespo; Khusaini, Moh. (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This study aims to (1) determine the relationship between the Nikkei 225 index, SSEC, STI, KLSE and JCI and (2) determine which capital market index movement has the dominant influence. This study uses the Nikkei 225 index, SSEC, STI, KLSE, and IHSG which are taken at the end of each month from January 2019 to February 2023. This study uses the VECM, IRF, and VD analysis methods. The research results obtained are (1) All short-term Asian stock indexes do not have the potential to infect the Japanese Index. In the long term, SSEC, STI, and JCI can infect the Nikkei 225, while KLSE does not have the potential to infect the NIKKEI 225. (2) All Asian stock indices in the short term have no potential to infect SSEC except NIKKEI 225. Only JCI can potentially infect SSEC in the long term, while STI and KLS have no contagion effect (3) There is no potential for short-term transmission to STI. For the long term, only NIKKEI 225, SSEC, and JCI can potentially to infect STI. (4) All Asian stock indices in the short term have no potential to be transmitted to KLSE. But in the long run, all of these Asian stock indices have the potential to spread to KLSE. (5) There is no potential for transmission in the short term to JCI. But in terms of transmission from NIKKEI 225 and SSEC. KLSE does not have a transmission effect on the JCI. (6) The dominant Asian stock index is the Nikkei 225, SSEC because this index is included in the index list with the largest market capitalization value in the Asian region.Keywords: globalization, asian capital markets, economic openness, contagion effect, shock